Digital Curation Centre – Phase Two - Helen Hockx-Yu (International Journal of Digital Curation, 2008)
An overview of the Digital Curation Centre since its establishment in 2004, including accomplishments of Phase One, aims and objectives of Phase Two, and how DCC relates to JISC strategy.